Blobjects and beyond : the new fluidity in design. - Skov Holt, Steven, ....-; Holt Skov, Mara, ....- (San Francisco : Chronicle, 2005)
A tie-in to major exhibition at the San Jose Museum of Art offers a comprehensive survey of the new fluidity of modern design, a style that emphasizes a turn away from hard edges and angles to celebrate an amorphic, organic, and curvaceous design.
Keywords: Industriële vormgeving